The susceptibility of FSHB -211G > T and FSHR G-29A, 919A > G, 2039A > G polymorphisms to men infertility: an association study and meta-analysis - Qiuyue Wu; Jing Zhang; Peiran Zhu; Weijun Jiang; Shuaimei Liu; Mengxia Ni; Mingchao Zhang; Weiwei Li; Qing Zhou; Yingxia Cui; Xinyi Xia (BMC, 2017)
Abstract Background Male infertility is a complex disorder caused by genetic, developmental, endocrine, or environmental factors as well as unknown etiology. Polymorphisms in the follicle stimulating hormone beta subunit (FSHB) (rs10835638, c.-211G > T) and follicle stimulating hormone receptor (FSHR) (rs1394205, c.-29G > A; rs6165, c.919A > G; rs6166, c.2039 A > G) genes might disturb normal spermatogenesis and affect male reproductive ability. Methods To further ascertain the aforementioned effects, we conducted a case-control study of 255 infertile men and 340 fertile controls from South China using the Mass ARRAY method, which was analyzed by the t-tests and logistic regression analysis using SPSS for Windows 14.0. In addition, a meta-analysis was performed by combining our results with previous reports using STATA 12.0. Results In the FSHB or FSHR gene single nucleotide polymorphism (SNP) evaluation, no statistically-significant difference was found in the frequency of allelic variants or in genotype distribution between cases and controls. However, a significant association for the comparison of GAA (P: 0.022, OR: 0.63, 95%CI: 0.43-0.94) was seen between the oligozoospermia and controls in haplotype analysis of rs1394205/rs6165/rs6166. In the meta-analysis, rs6165G allele and rs6166 GG genotype were associated with increased risk of the male infertility. Conclusions This study suggested that FSHR GAA haplotype would exert protective effects against male sterility, which indicated that the combination of three SNP genotypes of FSHR was predicted to have a much stronger impact than either one alone. Then in the meta-analysis, a significant association was seen between FSHR rs6165, rs6166 polymorphisms and male infertility. In terms of male infertility with multifactorial etiology, further studies with larger sample sizes and different ethnic backgrounds or other risk factors are warranted to clarify the potential role of FSHB and FSHR polymorphisms in the pathogenesis of male infertility.